LEGAL PRINCIPLES OF COMBATING CORRUPTION IN THE FIELD OF TAXATION AND THE PLACE OF ADMINISTRATIVE AND LEGAL NORMS AMONG THEM (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that the legislative basis for combating corruption in the field of taxation is formed at the level of the Constitution of Ukraine, the Tax Code of Ukraine and the Law of Ukraine "On Prevention of Corruption". However, the mere presence of the provisions of regulatory legal acts is not enough - their effective application requires independent and transparent implementation mechanisms. It is established that the importance of legal principles lies in the fact that they ensure the unity and consistency of legal regulation, contribute to stability in the state and determine guidelines for law-making, law-enforcement and judicial activities. Thanks to legal principles, conditions are created for the proper functioning of a legal state, in which human rights and freedoms are an integral part of the legislative system. They also serve as the basis for the legal protection of the interests of citizens, the development of democratic institutions and the strengthening of law and order in society. The emphasis is placed on the fact that legal principles are not static, they are constantly evolving, reflecting changes in society, the economy and international relations. It was found that administrative and legal norms occupy an important place among the legal principles of combating corruption in the field of taxation in Ukraine. They determine the basis of interaction between state authorities, in particular tax authorities, and taxpayers, creating a legal basis for monitoring compliance with tax legislation and preventing corruption in this area. It was emphasized that administrative and legal norms contribute to the prevention of corruption by establishing clear and transparent procedures for collecting, verifying and administering taxes. This reduces the possibility of abuse by both state authorities and taxpayers.
Keywords: legal principles; combating corruption in the field of taxation; administrative and legal norms; international standards; public control; administrative legislation